The bank-lending channel of monetary policy transmission in a dual banking system: empirical evidence from panel VAR modeling - Jamel Boukhatem; Mouldi Djelassi (Cogent Economics & Finance, 2022)
This paper applied the panel VAR approach and the Impulse Response Functions to investigate the differences in the monetary transmission processes of Islamic and conventional banks using disaggregated bank-level data for Saudi Arabia over the period 2008Q1-2020Q4. Our findings show that: i) Islamic banks play a significant role in transmitting monetary policy decisions to the real economy through the balance sheet channel; ii) Islamic banks' deposits are more responsive to oil price shocks than Islamic financing; iii) the reaction of Islamic banks to monetary policy and price shocks is relatively weaker than that of conventional banks, suggesting the existence of rigidities, such as excess liquidity, inertia in changing return rates, and the lack of funding and investment sources, and iv) the relatively significant responses of Islamic banks to various shocks make it easier for the Saudi central bank to achieve macroeconomic goals through monetary policy actions in a dual-banking system.
Keywords: C33; E44; E52; G21; 330; Bank lending channel; monetary policy transmission; Islamic banking; panel VAR